Novel 1,2,3-Triazole Compounds Containing Different Amine Groups: Synthesis, Characterization and in Silico Studies on Xanthine Oxidase - Tan, Ayşe (My University, 2022)
In this study, novel 1,2,3-triazole derivatives containing different amine subunits 16(a-c) and 17(a-c) were synthesized and characterized by FT-IR, HRMS, 1H, and 13C NMR analyses. The interactions with xanthine oxidase (XO) enzyme of these compounds were investigated with molecular docking studies. The obtained results were compared with molecular docking studies of allopurinol and febuxostat, which are the XO inhibitors. All target compounds demonstrated better binding energies than allopurinol in the interaction with the XO. On the other hand, 16a and 17a exhibited better binding affinities than febuxostat. The best binding energy values of the target compounds, allopurinol, and febuxostat vary between -6.1 and 9.84 kcal/mol. In this case, the target compounds may show better activity than allopurinol against the XO in vitro enzyme-inhibition studies. Additionally, compounds 16a and 17a may show better activities than febuxostat, as well. Finally, in silico ADME and toxicity studies for all target compounds were performed. The ADME results suggested suitable drug-likeness values for the compounds. Regarding toxicity, the compounds are predicted to be safe in terms of mutagenicity and tumorigenicity.